Drinking Horns in Old Norse Culture: A Tradition Under Examination - Hofmann, Anne (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2015)
By comparing archaeological finds with literary evidence this article seeks to reconstruct the role of drinking horns during the Viking Age. After an overview of drinking horns as represented in archaeology, several literary texts, predominantly Medieval Icelandic sagas, will be studied to shed further light on how drinking horns were seen and used. Drinking horns were used as a literary motif in these texts, but it can be demonstrated that they can also be linked to the archaeological evidence from the Viking Age, thus improving our understanding of the archaeological record.
Rogi do picia w kulturze ludzi Północy: Studium tradycji
Keywords: drinking horn; Old Norse; sagas; Viking Age; material culture